Ecology and Biotechnology of Microbial Nitrogen Fixation - Hauke Hennecke (CHIMIA)
Seventy-eight percent of the air we breathe in is molecular nitrogen (N2) – and the same amount we breathe out. Thus, human beings do not have the privilege of fixing N2. Rather, this is the domain of the diazotrophic bacteria. Without these bacteria life on earth would not be possible. On a global basis they replenish the nitrogen content in soil by about the same amount that is lost by the process called denitrification. This article describes some of the biochemical and genetic complexity of the nitrogen fixation process, and summarizes a few more recent data on the molecular basis of nodule induction on legumes by the rhizobia. Finally, a critical evaluation is presented on the perspective to utilize research on biological nitrogen fixation for practical application.